Economic Relations between Women and Their Partners: An East-West-German Comparison after Reunification - Heike Trappe; Annemette Sørensen (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
Women?s lives and opportunities in the economically advanced industrialized countries have changed dramatically during the last decades of the 20th century. One of the important implications of women?s increased labor force participation and intensity, their improved occupational qualifications and corresponding earnings capacity is that women?s economic dependence on male partners has declined. A decrease in women?s economic dependence would often be associated with an overall reduction of gender inequality within households as well as with changed power relations and would have important consequences for gender stratification in larger society. Some argue in the framework of bargaining theories that a decline in women?s economic dependence motivates male partners to invest additional time in housework (Jan Künzler, Wolfgang Walter, Elisabeth Reichart, and Gerd Pfister 2001) while others suggest that women?s greater economic independence enables them to invoke the threat of separation or divorce if a more favorable division of domestic duties cannot be negotiated (Lynn Prince Cooke 2004).
Keywords: 330; Haushaltsökonomik; Frauenerwerbstätigkeit; Wirtschaftliche Macht; Frauen; Männer; Lebensgemeinschaft; Vergleich; Neue Bundesländer; Alte Bundesländer